Steam : its generation and use. - Babcock and Wilcox company (New York : Merchant, 2007)
1927. Published by the Babcock and Wilcox Company, this is considered to be the most comprehensive text on steam production it includes: steam fundamentals, thermodynamics, heat transfer, metallurgy and design; steam generation, sources of energy, combustion, oil and gas, coal pulverization, cyclones, stokers, fluidized beds, superheaters, economizers, performance calculations and boiler enclosures; applications of steam, electric power, waste heat recovery, wood and biomass, marine applications; environmental protection, particulate control, nitrogen oxides and sulfur dioxide; specification, manufacturing and construction, equipment specification, economic and evaluation operation, pressure, temperature, steam quality and flow measurement, controls for fossil fuel-fired plants, water chemistry and treatment; maintenance and life extension; and also a section on nuclear energy steam generation, as well as SI units conversion factors.